The Efficacy of Isotonic and Hypotonic Intravenous Maintenance Fluid for Pediatric Patients. Issue 2 (February 2015) - Yang, Gang; Jiang, Wenjun; Wang, Xuejun; Liu, Wenying
<x xml:space="preserve">Abstract</x> Aim This study aimed to analyze the effect of isotonic versus hypotonic solution as intravenous maintenance fluid on level of plasma sodium in hospitalized children. Methods A fully recursive literature search in May 2013 was conducted in PubMed and EMBASE to identify potentially relevant randomized controlled trials. Jadad score and allocation concealment were adopted to evaluate the methodological quality of each trial. RevMan5.2 was used for statistical analysis. Results Eight randomized controlled trials with 752 patients were included. Combined analysis showed a significant lower risk of hyponatremia with isotonic solution (odds ratio, 0.36; 95% confidence interval, 0.26–0.51). The isotonic intravenous maintenance did not increase the possibility of hypernatremia (odds ratio, 0.86; 95% confidence interval, 0.36–2.06). Conclusions The meta-analysis revealed that there was potential risk of hyponatremia for routine infusion of hypotonic maintenance fluid. The use of isotonic solution was warranted in hospitalized pediatric patients.